The Importance of Intellectual Capital In Driving Firm Performance - Halim, Kusuma Indawati (Universitas Negeri Semarang, 2023)
Purpose: The study explores the structure of intellectual capital and how it influences firm performance of Kompas 100 Index companies using the VAIC model. Method: As research samples, 29 companies from the Kompas 100 index that were listed on the Indonesian Stock Exchange were employed. The data came from annual reports that were released between 2017 and 2021. A multiple regression analysis was used to create the regression model for this study. Findings: It can be observed that VAIC has a significant positive effect on both ROA and ROE. Based on each component of VAIC, it is clear that HCE, SCE, and CEE have a positive and significant impact on firm performance. By setting spesific targets and regularly monitoring these neasures, businesses can identify areas for improvement and make informed decisions to enhance their firm performance. Novelty: The findings are especially significant for policymakers that want to emphasize the value of Intellectual Capital and create a system for disclosing Intellectual Capital. This study also offers up new paths for future research that will take into consideration the dynamic nature of the relationship between Intellectual Capital and Firm Performance and account for endogeneity. Keywords: Human Capital Efficency; Structural Capital Efficiency; Capital Employed Efficiency; Value Added Intellectual Coefficient